GESTÃO ESCOLAR NA ESCOLA PÚBLICA: interfaces entre gerencialismo e gestão democrática - Clemente, Josafá da Conceição (2015)
This dissertation deals with the School Management in Public School: interfaces between managerialism and democratic management with a view to grasp the concept of school management that guides the management practices at a school public schools in Sao Luis, Maranhão. The methodology guides in the historical and dialectical materialism and uses literature, documentary and field, supported by survey of empirical data by carrying out semi-structured interviews applied to a sample of 35 subjects whose information made it possible to expand the knowledge about reality social experienced by the public school and its relations with the social and educational context, materialized by the recognition of contradictory discourses of the subjects in the effectiveness of school management policies. Among the authors who have referred the present study, include: Marx (1979), Gramsci (1999), Piotte (1975), Kosik (1976), Gruppi (1978), Oliveira (2010), Cabral Neto (2007), (2009), (2011), Libâneo (2012), Ferreira (2006), Savianni (2001), (2007), Dourado (2001), (2006), Frigoto (1999), (2003), among others. The argumentative text is divided into sections, the first being reserved for initial demarcation of the object, the objectives and guiding questions, the methodological approach and organization of the text. Second, we analyze the changes resulting from technical and scientific progress and its impact on the setting of education policy and management education. In the third, it reflects on the administration concepts and school management in the Brazilian educational system. In the fourth section, education management policies up approach in the state of Maranhão and performs the characterization of management practices in a school of public schools. The reality observed revealed that educational school management policies account for more control maintenance possibilities of the education system, the results, the relaxation, the goals and indicators of the effectiveness of autonomy, participation, collective interest and democratization coming a democratic perspective. It was concluded that the reality researched walks more aligned to the control of managerial conceptions of what the democratic participatory guidelines.